Stratifikasi Sosial dalam Novel Pasar Karya Kuntowijoyo - Mila Subana Safitri; Nurizzati Nurizzati (Persona: Kajian Bahasa dan Sastra, 2022)
This study focuses on the social stratification system of Javanese society using Koentjaraningrat's theory which states that Javanese society is divided into four groups, namely dharai (nobles), priyayi (bureaucrats), wong dagang (traders) and wong cilik (little people, small people). This study aims to describe: (1) the forms of social stratification in Kuntowijoyo's novel Pasar, (2) the factors causing social stratification in Kuntowijoyo's novel Pasar, and (3) the impact of social stratification in Kuntowijoyo's novel Pasar. This type of research is a qualitative research using descriptive methods with content analysis techniques. The data in this study are in the form of words, phrases, clauses, and sentences that indicate social stratification in Kuntowijoyo's novel Pasar. The data collection technique is reading and understanding the novel, marking data related to research problems to gain a deeper understanding of the problem, and take inventory (search) data. Validation of the data in this study using triangulation techniques. or merchants (traders), and wong cilik (ordinary people). The factors that cause social stratification in Kuntowijoyo's novel Pasar are wealth, power, honor, and knowledge. The impact is social conflict and competition.